Spatial and Temporal Distribution of Skipjack and Little Tuna in Fisheries Management Area 713 - Safruddin, Safruddin; Hidayat, Rachmat (Hasanuddin University, 2023)
Indonesian Fisheries Management Area (IFMA) 713 is a strategic and potential area for utilizing large pelagic fishery resources. In general, there are no fixed fishing grounds for large pelagic fish, and they are always changing and moving following the movement of environmental conditions, which naturally causes fish to choose a more suitable habitat. This study examines the distribution and abundance of skipjack tuna (Katsuwonus pelamis) and little tuna (Euthynnus sp) in relation to oceanographic conditions such as the distribution of sea surface temperature and sea surface chlorophyll-a concentrations in Indonesian Fisheries Management Area 713, which includes the Makassar Strait, Flores Sea, and Bone Bay. Based on the findings, skipjack tuna tends to be caught at warmer temperatures and higher chlorophyll-a concentrations than little tuna. Skipjack tuna tended to be distributed at a temperature of 29.84°C-30.28°C, which was associated with a chlorophyll-a concentration of 0.3 mg m-3, in contrast to little tuna, which was distributed at a temperature of 27.92°C-28.66°C with the most productive chlorophyll-a concentration (relatively high CPUE) of 0.2 mg m-3. This information on habitat distribution and optimum conditions of oceanographic parameters is very useful for the sustainable management of skipjack tuna and little tuna in the IFMA 713. in contrast to little tuna, which was distributed at a temperature of 27.92°C-28.66°C with the most productive chlorophyll-a concentration (relatively high CPUE) of 0.2 mg m-3. This information on habitat distribution and optimum conditions of oceanographic parameters is very useful for the sustainable management of skipjack tuna and little tuna in the IFMA 713. in contrast to little tuna, which was distributed at a temperature of 27.92°C-28.66°C with the most productive chlorophyll-a concentration (relatively high CPUE) of 0.2 mg m-3. This information on habitat distribution and optimum conditions of oceanographic parameters is very useful for the sustainable management of skipjack tuna and little tuna in the IFMA 713.